2015
DOI: 10.11113/jt.v78.3090
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Sustainable Manufacturing Practices on Sustainability

Abstract: This study aims to empirically investigate the impact of sustainable manufacturing practices (SMP) on sustainability performance (SP) among manufacturing firms in Malaysia. Drawing from the theoretical lenses of stakeholder theory, the present study advocates the three pillars of sustainability, encompassing economic, environmental, and social sustainability, in measuring firm performance. Using PLS-SEM approach, the survey data collected from 150 firms were analyzed. The findings reveal that both underlying v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 28 publications
0
14
1
Order By: Relevance
“…Although there is no empirical support for the direct relationship between EL and ECSPF, this finding is in contrast with [85], who stated that EL is positively influencing acquisition performance, which indirectly influences economic performance through returns on investment, sales, and equity. This finding also contradicts the previous literature which stated that sustainable practices positively enhance economic performance [22,57,86]. The authors found that by being friendly to the environment and responsible to employees, society, as well as suppliers, a better market position and business performance may be attained for a business.…”
Section: Theoretical Contributioncontrasting
confidence: 64%
See 3 more Smart Citations
“…Although there is no empirical support for the direct relationship between EL and ECSPF, this finding is in contrast with [85], who stated that EL is positively influencing acquisition performance, which indirectly influences economic performance through returns on investment, sales, and equity. This finding also contradicts the previous literature which stated that sustainable practices positively enhance economic performance [22,57,86]. The authors found that by being friendly to the environment and responsible to employees, society, as well as suppliers, a better market position and business performance may be attained for a business.…”
Section: Theoretical Contributioncontrasting
confidence: 64%
“…Most previous studies relate sustainable performance with sustainable manufacturing practices [44,57], green supply chain practices [43][44][45][46][47], environmental management systems i.e., the international standard ISO 14001 and the European EMAS scheme [58], strategic purchasing, and sustainable supply management [48]. Thus, empirical research that examines the relationship between sustainable performance and EL is scarce.…”
Section: Entrepreneurial Leadership and Sustainable Performancementioning
confidence: 99%
See 2 more Smart Citations
“…In this respect, sustainable manufacturing practices (SMPs) have not been widely studied and documented by researchers (Alayón et al, 2017;Despeisse et al, 2012;Roberts and Ball, 2014). Additionally, several empirical evidence suggests that SMPs contribute to improved economic, environmental and social sustainability (e.g., Abdul-Rashid et al, 2017a;Abdul-Rashid et al, 2017b;Gimenez et al, 2012;Habidin et al, 2013;Hami, 2015;Hami et al, 2016;Hartini and Ciptomulyono, 2015;Shubham et al, 2018;Zubir et al, 2012). Therefore, there is a necessary need to study SMPs as they will contribute to addressing the practical issue of SP in the O&GI in Iraq.…”
Section: Introductionmentioning
confidence: 99%